PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI KELAS X DI MAN 2 TANAH DATAR - Sagita Fathuloh Martadyna; Afdhal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the persistently low student learning outcomes in Geography, consequently, there is a need to implement a learning model capable of enhancing student engagement and academic performance. The study aimed to assess student learning outcomes before and after the implementation of the Snowball Throwing learning model and to determine the model's impact on the Geography learning outcomes of Grade X students at MAN 2 Tanah Datar. A quantitative approach was employed, utilizing a quasi-experimental design with a pretest-posttest control group structure. The research sample consisted of an experimental class and a control class, selected via purposive sampling. Data were collected through learning outcome tests (pretest and posttest) and analyzed using normality tests, homogeneity tests, and the Independent Samples t-test. The results indicated that student learning outcomes were initially low but showed a significant improvement following the implementation of the Snowball Throwing model. Hypothesis testing confirmed that the Snowball Throwing learning model had a significant effect on student learning outcomes. Thus, the Snowball Throwing learning model serves as an effective alternative for improving student learning outcomes.